Fabrication of Polyimide Optical Waveguide on Silicon Dioxide Layer Stacked Silicon Substrate - Dadin Mahmudin; Shobih -; Pamungkas Daud; Yusuf Nur Wijayanto (Jurnal Elektronika dan Telekomunikasi, 2017)
Optical waveguides are important for guiding lightwave from a place to other places. Propagation and insertion losses of the optical waveguides should be considered to be in low values. Recently, optical waveguides with circular structures, which are optical fibers, are used widely for guiding lightwave in long-distance optical communication with very low propagation and insertion losses. Simultaneously, optical waveguides with planar structure are also developed for short distance communication in optical devices. We have reported design and analysis of the planar optical waveguides. In this paper, fabrication of planar optical waveguides using a polyimide material on thin silicon dioxide combined with the silicon substrate is reported. The polyimide material is used for the core of the optical waveguides. The silicon dioxide located on the silicon substrate and the air is used for cladding of the optical waveguides. Fabrication of the optical waveguides such as oxidation, photoresist coating, masking, ultra-violet exposure, and etching was done. The fabricated optical waveguides were characterized physically using a standard microscope and scanning electron microscope (SEM). The fabrication processes and characterization results are reported and discussed in detail.